Direito de imagem e direito de arena no contrato de trabalho do atleta profissional - Soares, Jorge Miguel Acosta (2007)
The purpose of this study was to deepen the current knowledge about employment contracts of football players or professional athletes. With the experience gained in the Union, a reflection was sought about four aspects of those contracts which permitted, after data systematization and exploration, a description, the definition of limits and consequently an in-depth analysis of the matter under study. Those aspects were: the historical evolution of this profession and of its legislation, the various views of the doctrine about the legal nature of such contracts, the Image Right and the Arena Right. A research about the historical evolution of the employment contract of this kind of athlete pointed out that the specific legislation for this category advanced very slowly. An analysis of the historical process revealed that the social gains obtained by the workers with the restatement of the labor laws early in the 40s only started to be enjoyed by football players half a century later, suggesting that the problems experienced by those athletes have their roots in the past history of that category. In parallel to the legislative history, the various formulations produced by the legal doctrine about the athlete and the athlete's contract with a club were also studied. Further, a brief description of the various conceptions of the doctrine makers about the legal nature of such contracts is also given. Then the issues relating to the Image Right are discussed, seeking an understanding of its insertion in the realm of the Personality Rights, as well as its new positioning as given by the 1988 Federal Constitution. The Maximum Law ascribed neverseen- before guarantees to those rights, an innovation even in relation to the most modern constitutions worldwide. The new constitutional approach to the Image Right has raised significant issues for the athlete category. The treatment now given to it has imposed a new reality to the clubs, forcing them to review old practices involving image assignment contracts, usually when signing up the athlete. Lastly, a study is conducted about the Arena Right, a figure created in Brazil with no similar elsewhere, and which is a relevant source of revenues for clubs and equivocally confounded with the Image Right. This study shows that those two rights are getting apart diametrally; they are different rights, with different title holders and diverse legal nature, although, mostly, they are considered as equivalent